A clinical review of elbow ligament repairs and reconstructions in the acute and chronic settings - Christopher T. Ling, MBChB; Adam W. Durrant, FRACS; Michael Foster, FRACS; Amy Wang, MHPrac; Juma Rahman, MBBS, PhD; Wolfgang Heiss-Dunlop, FRACS (JSES International, 2024)
Background: The ligamentous and osseous structures of the elbow joint are the major contributors to its inherent stability and damage to any of these structures can result in elbow instability. The aim of this study is to present objective and subjective outcomes following ligament repairs and/or reconstructions for acute elbow instability and chronic elbow instability. Methods: This study included patients who underwent an elbow ligament repair and/or reconstruction for acute or chronic elbow instability. We performed a comprehensive retrospective data analysis of the patient's files, followed by a clinical examination and X-ray of these patients. Results: We identified 12 acute stabilizations and 22 stabilizations for chronic instability. Patients who underwent stabilization for chronic instability had statistically significant improvements in their preoperative flexion and extension; 14.8 ± 6.4° and 5.9 ± 2.5°. Patients with chronic instability achieved better extension-flexion and pronation-supination arcs compared with their acute instability counterparts and this reached statistical significance. When the elbow pain and function scores were compared, we found stabilizations in the acute setting had better outcomes. There were two cases of postoperative instability, one in the acute instability group and one in the chronic instability group. Conclusion: This study provides evidence for elbow ligament repairs and reconstructions in both acute and chronic settings. It is an effective way of stabilizing the elbow joint in chronic instability patients, and results in an improvement in their overall range of motion. These patients achieved a greater range of motions compared with their acute instability counterparts.